2021
DOI: 10.2147/opth.s236423
|View full text |Cite
|
Sign up to set email alerts
|

Managing Diabetic Macular Edema in Clinical Practice: Systematic Review and Meta-Analysis of Current Strategies and Treatment Options

Abstract: Purpose This meta-analysis aims to summarize 12-month best-corrected visual acuity (BCVA) outcomes in response to anti-vascular endothelial growth factor (VEGF) therapy and dexamethasone implant for the treatment of diabetic macular edema (DME) and to identify factors affecting treatment response using evidence generated from meta-regression. Methods A systematic review of electronic databases was conducted to identify randomized controlled trials (RCTs) and real-life/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…However, their study included a limited number of trials. Recently, Veritti et al 67 published a meta-analysis discussing the strategies and treatment options for DME. They included 45,032 eyes from RCTs and observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, their study included a limited number of trials. Recently, Veritti et al 67 published a meta-analysis discussing the strategies and treatment options for DME. They included 45,032 eyes from RCTs and observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…DME is the main cause of vision loss among patients with diabetes worldwide (9) and, with progressive population aging, a greater burden of this disease is expected in the coming years (8). In the last few years, the treatment of this eye disease has been revolutionized by the introduction into clinical practice of intravitreal therapy with anti-VEGF agents and corticosteroid implants (11). Anti-VEGFs, such as ranibizumab, aflibercept and bevacizumab-the latter used as an off-label treatment-have proved much more efficacious than the previous standard of care (laser photocoagulation), achieving clinically relevant improvements in visual acuity (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the European Society of Retina Specialists (EURETINA) guidelines, focal/grid laser therapy is now reserved mostly for non-center-involving DME (10). In recent years, the introduction into clinical practice of intravitreal therapy with vascular endothelial growth factor inhibitors (anti-VEGFs) and corticosteroid implants has revolutionized the medical management of DME (11). Indeed, these treatments result in a significant improvement in the bestcorrected visual acuity (BCVA) at 12 months in patients with DME (11).…”
Section: Introductionmentioning
confidence: 99%
“…4 PRN regimen is commonly adopted. 15,17,18 However, frequent clinical visits for monitoring recurrence is needed. Recent treat-and-extend studies have showed that approximately 41% to 67% of patients were able to extend their injection interval to ≥16 weeks at two years, while other patients still required frequent injections in four to 12week intervals.…”
Section: Discussionmentioning
confidence: 99%